Fatal poisoning case involving drug interaction due to the inhibition of cytochrome P450 - Kinoshita, Hiroshi; Tanaka, Naoko; Kumihashi, Mitsuru; Jamal, Mostofa; Ito, Asuka; Yamashita, Tadayoshi; Ameno, Kiyoshi (Vojnosanitetski pregled, 2021)
Introduction. Cytochrome P450 (CYP) enzymes are responsible for the metabolism of various drugs and chemicals. The forensic pathologist should consider not only pharmacodynamic interactions by multiple drugs but also the pharmacokinetic drug interactions of each drug in the case of multiple drug ingestion. Case report. A female in her forties, receiving therapy for alcohol dependence, was found dead in her house. The medicolegal autopsy revealed no findings suggestive of natural cause of death. Quantitative toxicological analysis showed that levomepromazine, promethazine, dextromethorphan, estazolam, clomipramine, risperidone, and flunitrazepam concentrations in femoral blood were 0.750 µg/mL, 0.701 µg/mL, 0.332 µg/mL, 0.390 µg/mL, 0.216 µg/mL, 0.031 µg/mL, and 0.002 µg/mL, respectively, along with a blood ethanol level of 377 mg/dL. Conclusion. We concluded that the cause of death was the interaction between ethanol and multiple psychotropic drugs. Pharmacokinetic drug interactions due to the CYPs inhibition should be considered in the evaluation of toxicity in poisoning cases involving multiple drugs.
Keywords: autopsy; cytochrome p-450 enzyme system; drug interactions; ethanol; forensic pathology; phenothiazines; poisoning; psychotropic drugs